Transforming Semarang: The Legacy of Thomas Karsten in Urban Planning and Architecture - Indarti, Fitri Dwi; Azzahra, Anugrah Olivia (Architecture Study Program, Faculty of Engineering and Computer Science, Universitas Muhammadiyah Semarang, 2024)
The concept of urban planning in the 19th century was differentiated through traditional and modern approaches, but the impact of the Industrial Revolution created new relationships between Urban Planning and other Urban Arrangements such as economic pressures, social and political changes, and urbanization. Before the influence of the Industrial Revolution, industry did not arise in urban areas, but industry grew in the suburbs. The development of Semarang began to grow when the economic system first affected modern capitalism. Many traditional institutions are slowly being replaced by more contemporary ways. According to Thomas Karsten, society is formed by different groups, each with conflicts between themselves, his analysis of this social tendency can be seen in the urban planning process he carried out. The concept is centered on a particular whole, a continuum of organisms in the form of an organic whole. The four main ethnic groups that lived in Semarang during the colonial era were: the Dutch and other Europeans, Chinese, Arabs, and Javanese. By accepting conventions, they live in separate groups according to race. During Karsten's first experience in urban planning, he developed an alternative to this acceptable system that could be applied in Semarang. He introduced the idea of a residential division represented by certain types of housing based on economic status classes such as upper, middle, and lower. He tried to bring different races to live together in the same place when judging from their earning ability. He also pays special attention to Indonesia's tropical climate and emphasizes features that contribute to the overall urban space, such as the planting of vegetables and trees, and the planning of low-density residential areas.